Barriers to the implementation of Solar PV Technology for tourism industry in Malaysia / Nurhidayah Samsul Rijal ... [et al.] - Samsul Rijal, Nurhidayah; Ahmad, Nur Azfahani; Abd Rased, An Nisha Nur Welliana; Mohd Talmizi, Nurain; Ali, Nor Eeda (2022)
Demand for fossil fuels in Malaysia is increasing due to the rapid development in the industrial and tourism sectors. Conventional energy used today is a non-renewable resource that will eventually run out. To fulfil rising conventional energy demand, the global energy sector has begun to shift its focus to renewable energy. Solar energy is one of the sources that has a bright future as an alternative to replace conventional energy in electricity generation. Solar Photovoltaics (PV) is seen as one of the positive alternatives in empowering green technology for the sake of environmental well-being. Malaysia should be able to generate electricity based on sunlight sources as we are endowed with an equatorial climate which is hot and humid all year round. However, this technology is not yet widely used, especially in the tourism sector. This study aims to identify and analyse the barriers and challenges faced by tourism industry stakeholders in the implementation of Solar Photovoltaics (PV) technology to form a sustainable tourism industry in Malaysia. This study used descriptive research approach. The result shows cost is the main difficulties for implement this technology. The findings also can help give a true picture of the obstacles faced by tourism industry stakeholders in the implementation of this solar technology in the tourism industry.